A graphical representation of an estimated DSGE model. Issue 6 (1st February 2016) - Jones, Callum; Kulish, Mariano
ABSTRACT: We write a New Keynesian model as an aggregate demand curve and an aggregate supply curve, relating inflation to output growth. The graphical representation shows how structural shocks move aggregate demand and supply simultaneously. We estimate the curves on US data from 1948 to 2010 and study two recessions: the 2001 recession and the Great Recession of 2008–2009. The Great Recession is explained by a collapse of aggregate demand driven by adverse preference and permanent technology shocks, and expectations of low inflation.